Spatial and Temporal Variability of Soil pH, Organic Matter and Available Nutrients (N, P and K) in Southwestern China - Bao-Xiu Guo; Jia Zhou; Lin-Qing Zhan; Zi-Yu Wang; Wei Wu; Hong-Bin Liu (Agronomy, 2024)
Knowledge of the spatial and temporal variations in soil nutrients is crucial for designing efficient site-specific nutrient management plans, which can improve crop yields and maximize nutrient use efficiency. The present study was conducted to evaluate and compare the status and spatio-temporal distribution pattern of available nitrogen (AHN), phosphorus (AP) and potassium (AK) and some selected soil properties [soil pH and soil organic matter (SOM)] in cultivated soils of Southwestern China over a 15-year period (2007–2022). We visualized the correlations among soil properties, AHN, AP and AK and analyzed the spatial structures of these parameters. A total of 3845 topsoil (0–20 cm) samples (3331 in 2007 and 514 in 2022) were collected from the cultivated areas of Jiangjin District, Chongqing, Southwestern China. Soil pH, SOM, AHN and AK showed moderate variability with coefficient of variation (CV) values varying between 10 and 100%, except AP (CV > 100%, high variability). The mean soil pH, SOM, AP and AK in 2022 were significantly higher than those in 2007. AHN was significantly positively correlated with SOM (r = 0.531, p < 0.01 in 2007, r = 0.768, p < 0.01 in 2022) and significantly negatively correlated with soil pH (r = −0.186, p < 0.01 in 2007, r = −0.102, p < 0.05 in 2022). AP was significantly negatively correlated with soil pH (r = −0.075, p < 0.01 in 2007, r = −0.126, p < 0.01 in 2022). AK was significantly positively correlated with SOM (r = 0.164, p < 0.01 in 2007, r = 0.229, p < 0.01 in 2022), ANH (r = 0.131, p < 0.01 in 2007, r = 0.251, p < 0.01 in 2022) and AP (r = 0.145, p < 0.01 in 2007, r = 0.52, p < 0.01 in 2022). The exponential function performed best for the soil properties and all three nutrients, with higher R2 values (0.203 to 0.93 in 2007 and 0.316 to 0.796 in 2022) in both years. The nugget/sill ratios (which varied from 31.58% to 72% in 2007 and from 29.31% to 47.02% in 2022) indicated the moderate spatial dependence of all soil parameters, except AK in 2022 (nugget/sill ratio = 23.81%, strong spatial dependence). During the study period, soil pH, AP and AK increased in the central and northern areas; SOM increased in the northern and southwestern parts; AHN decreased in the central areas. The current study highlighted the change in spatial variability of soil pH, AHN, AP and AK in the study area over 15 years.